The Effect Various of Kinds Organic Fertilizer On Gaharu Seedling (Aquilariamalaccesis LAMK) In The Field - Annadira; Ridwan; Muslimin (Agricultural Science, 2023)
This research aims to determine the effect of various types of organic fertilizer on the growth of agarwood seedlings (aquilaria malaccensis lamk). This research was conducted in August to November 2022. This study was conducted at Arboretum of the Faculty of Forestry. Tadulako University Palu. This research uses a complete random design (RAL) consisting of 3 treatments namely K1 (Control) K2 (DOAMI Organic Fertilizer) K3 (Gresik Organic Fertilizer). The results showed that the administration of various types of organic fertilizer had a significant effect on high increase and seedling diameter, but did not significantly affect the increase in the number of leaves. K2 treatment gives better results than other treatment. Average of seed height K1 = 4.5, K2 = 7.75 k3 = 6.75, the average increase in the diameter of the seedlings is K1 = 0.37 K2 = 0.72 k3 = 0.45. The average increase in the number of leaves of K1 = 6, K2 = 10.25, K3 = 7.75.